Transcriptomic profiling of “brain-eating amoeba” Naegleria fowleri infection in mice: the host and the protozoa perspectives - Guerlais, Vincent; Allouch, Nina; Moseman, E. Ashley; Wojciechowska, Alicja W.; Wojciechowski, Jakub W.; Marcelino, Isabel (Frontiers in Cellular and Infection Microbiology, 2024)
The free-living amoeba Naegleria fowleri (NF) causes a rare but lethal parasitic meningoencephalitis (PAM) in humans. Currently, this disease lacks effective treatments and the specific molecular mechanisms that govern NF pathogenesis and host brain response remain unknown. To address some of these issues, we sought to explore naturally existing virulence diversity within environmental NF isolates. Herein, we purified two new NF environmental isolates (NF45 and NF1) and tested their in vivo virulence using experimental infection in mice. We found that NF45 was highly virulent (NF45_HV) compared with NF1 (low virulence, NF1_LV), based on in vivo amoeba growth kinetics and mouse survival. To identify underlying differences, we conducted RNA-seq and bioinformatics analyses from the infected mouse brains. Our results showed that NF1_LV and NF45_HV modulated the expression of their genes during mouse brain infection. Differentially expressed genes (DEGs) in NF1_LV were mostly involved in Translational protein, Protein-binding activity modulator, Protein modifying enzyme, while DEGs in NF45_HV were related to DNA metabolism, Cytoskeletal protein, Protein-binding activity modulator. Proteases (namely the virulence factor Cathepsin B) were upregulated in NF1_LV, while downregulated in NF45_HV. When analyzing the host response against infection by these two NF strains, enrichment analyses uncovered genes and mechanisms related to the host immune responses and nervous systems. We detected more DEGs in NF1_LV infected mice compared to NF45_HV, related to blood brain barrier leakage, immune cell recruitment, cytokine production (including IL-6, IFN-Ɣ and TNFα), inflammation of astrocytes and microglia, and oligodendrocyte and neurons degeneration. Increased expression of neuromotor-related genes such as Adam22, Cacnb4 and Zic1 (activated by NF1_LV infection) and ChAt (activated by NF45_LV infection) could explain PAM symptoms such as muscle weakness and seizures. Globally, our results showed that NF isolated from the environment can have different levels of virulence and differentially modulate their gene expression during brain infection. We also provided, for the first time, a comprehensive information for the molecular mechanisms of neuro-immune and host–pathogen interactions during PAM disease. As the host and the protozoa are strongly implicated in PAM lethality, new therapies targeting both the parasite, and the host should be considered to treat PAM infection.